Fecal microbiota transfer to treat ulcerative colitis: Medical and legal challenges - Steube, Arndt; Stallhofer, Johannes; Stallmach, Andreas (Frontiers in Gastroenterology, 2023)
Ulcerative colitis (UC) is one of the main forms of chronic inflammatory bowel disease; however, despite intensive efforts, its etiology remains unclear. It is generally accepted that disturbances in the gastrointestinal microbiota (“dysbiosis”) contribute to the manifestation and perpetuation of UC. To date, treatment has focused on anti-inflammatory strategies; however, their widespread application is limited by side effects and primary/secondary loss of response. Following the resounding success of fecal microbiota transfer (FMT) to treat Clostridioides difficile infection (CDI), numerous studies have shown that FMT is also effective and safe in UC patients. In this review, we discuss the various modifications (e.g., antibiotic preconditioning, multi-donor concept, extension/intensification of application, long-term therapy, and dietary donor conditioning) that increase the efficacy of FMT. We then describe how the continuous need for healthy donors and the associated medicolegal requirements, limit the large-scale application of FMT. We conclude that FMT will likely be viewed as a transitional technology, which will be superceded by recombinantly produced bioproducts once the therapeutically active substances have been identified.